Clericalism: the death of priesthood - Wilson, George B. (Liturgical Press, 2008)
Introduction: "Priest" and "cleric" -- Clarifying the terminology -- Cultures, clergies, and the priesthood -- Clerical cultures and how they "work" -- Priesting before clergyhood -- When priests become ordained clergy -- Tragedy and transformation -- The sexual abuse tragedy -- And the clergies that enacted it -- Transformation -- Re-priesting a clericalized church -- Expectations of the ordained and the laity